On a New Application of Positive and Decreasing Sequences to Double Fourier Series Associated with (N, p^(1)_m, p^(2)_n) - Sahani, Suresh Kumar; Paudel, Gyan Prasad; Thakur, A. K. (Journal of Nepal Mathematical Society, 2022)
In this paper, we introduce a new application of positive and decreasing sequences to double Fourier series associated with (N, pm(1) ,pn(2)). Further, by considering some suitable conditions for previously known results, we have validated the current findings. This work is motivated by the works of [5] and [12].